2020
DOI: 10.21608/eajbsa.2020.110344
|View full text |Cite
|
Sign up to set email alerts
|

Fall Armyworm Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae) Biological Aspects as A New Alien Invasive Pest in Egypt

Abstract: The present study may be the first attempt in Egypt which devoted to studying the biological aspects of fall armyworm, Spodoptera frugiperda (J.E. Smith). The study was conducted under laboratory conditions (26 ±1°C and 65 % R.H.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Results indicated that maize leaves could be considered as a more favorable food material to rearing of S. frugiperda. These results agree with findings by Gamil 2020, Guo et al, 2021and Maha et al, 2024 Also, artificial diet can be considered a suitable food source to S. frugiperda larvae as it, successfully, complete their life on it and succeeded in laying fertile eggs (87.38% hatchability). It can also be arranged favorable food material to rearing of S. frugiperda, as follows: maize, artificial diet, rice, pea and tomato.…”
Section: The Effect Of Feeding Larvae Of S Frugiperda On Four Plant L...supporting
confidence: 91%
“…Results indicated that maize leaves could be considered as a more favorable food material to rearing of S. frugiperda. These results agree with findings by Gamil 2020, Guo et al, 2021and Maha et al, 2024 Also, artificial diet can be considered a suitable food source to S. frugiperda larvae as it, successfully, complete their life on it and succeeded in laying fertile eggs (87.38% hatchability). It can also be arranged favorable food material to rearing of S. frugiperda, as follows: maize, artificial diet, rice, pea and tomato.…”
Section: The Effect Of Feeding Larvae Of S Frugiperda On Four Plant L...supporting
confidence: 91%
“…The fall armyworm, Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae), is one of the major invasive polyphagous pests that habitat more than 353 plant species, especially maize, sorghum, sugarcane, turfgrass, cotton, and vegetable crops (Montezano 2018 ; Gamil 2020 ; Timilsena et al 2022 ). Since 2016, S. frugiperda has spread rapidly over 44 countries in West Africa (Day et al 2018 ; Kassie et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since 2016, S. frugiperda has spread rapidly over 44 countries in West Africa (Day et al 2018 ; Kassie et al 2020 ). In Egypt, S. frugiperda was first recorded on maize fields in 2019 in Komombo, Aswan Governorate (Food and Agriculture Organization (FAO) 2019 ; Dahi et al 2020 , Gamil 2020 ). Thereafter, it overspread Upper Egypt governorate towards the north on maize and sorghum crops in 2021 (Mohamed et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The invasion process typically occurs in three distinct phases [31]. First, it involves the introduction of a non-native species to an area outside of its original habitat, often facilitated by human activities such as trade, urbanization, and infrastructure development [32]. The second phase entails the establishment of stable populations, supported by either a higher intrinsic growth rate [33] or superior competitive ability compared to native species [34].…”
Section: Discussionmentioning
confidence: 99%